Wartości patriotyczne w doświadczeniu polskich migrantów w Wielkiej Brytanii - Adamczyk, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The aim of the article was to show patriotic values in the experience of Polish migrants in Great Britain. The empirical material collected using the qualitative research method using in-depth interview technique was analyzed. The material was analyzed taking into account three issues: a sense of pride in being a Pole, attitude towards the homeland and the ways of maintaining and developing Polishness. Sociological analysis has shown that in multicultural societies, changes in patriotic values occur in different directions. In some migrants, they disappear, while in others they are cultivated, discovered and even developed.